Consideraciones sobre el programa de Farmacología General en el plan de estudio D para la carrera de medicina. - Peacok Aldana, Sandra; Cala Calviño, Leidys; Labadié Fernández, Sandra; Sollet Medina, Kenia Rosa; Gámez Fernández, Yasley (MEDISAN, 2021)
The syllabus, fundamental document that establishes the general direction and the main content of the professionals training, has been continually improving, in correspondence with the scientific technical development achieved. The subject program is the one that reflects its most important characteristics; it has scientific and pedagogic validity and contributes to the general doctor training, according to the demands of the present Cuban society. Taking into account the previous considerations this study was carried out aimed at analyzing the theoretical and methodological elements of the General Pharmacology subject program in the syllabus D for the medicine career.